Pathways to retirement and the role of financial incentives in Sweden - Per Johansson; Lisa Laun; Mårten Palme (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2014)
We study how economic incentives affect labor force exit through different income security programs, old-age pensions as well as income taxes in Sweden. We use the option value for staying in the labor force as a measure of economic incentives and estimate an econometric model for the choice of leaving the labor market. Besides old-age pension, we focus on the Disability Insurance (DI), which is the most important exit path before age 65. By simulating the effect of different probabilities to be admitted DI we show how changes in the stringency of DI admittance affects labor supply among older workers through economic incentives.
Keywords: H55; J14; J26; 330; disability Insurance; option value; labor market exit; labor supply